Therapeutic Potential of White Sweet Potato Peel in Enhancing Insulin Production and The Proliferation of Beta Cells in Diabetic Rats - Aan Royhan; Rina Susilowati; Sunarti Sunarti (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2026)
Diabetes mellitus (DM) affects approximately 422 million people worldwide, predominantly in low- to middle-income countries, and is associated with increasing morbidity and mortality. The long-term use of conventional antidiabetic drugs may cause adverse effects, prompting interest in natural therapeutic alternatives. This study aimed to evaluate the effects of white sweet potato peel (WSPP) on glycemic control, insulin expression, and pancreatic beta-cell proliferation in streptozotocin-induced diabetic rats. Male Wistar rats were divided into five groups: diabetic control, diabetic rats treated with WSPP at doses of 400, 800, and 1600 mg/kgBW/day, and non-diabetic controls. Diabetes was induced by a single intraperitoneal injection of streptozotocin (60 mg/kgBW). Fasting blood glucose (FBG) levels were measured at baseline and during treatment. Pancreatic tissues were analyzed using immunohistochemistry to assess insulin expression, Langerhans islet area, and beta cell proliferation using anti-insulin and anti-PCNA antibodies. WSPP administration resulted in a significant, dose-dependent reduction in FBG levels compared to diabetic controls (p < 0.05). The highest dose (1600 mg/kgBW/day) reduced FBG from approximately 250 mg/dL to 72.22 mg/dL after four weeks (p < 0.01), reaching the normal range. Immunohistochemical analysis demonstrated significant increases in insulin expression scores, Langerhans islet area, and the percentage of PCNA-positive cells in the 800 and 1600 mg/kgBW/day groups compared to untreated diabetic rats. At the highest dose, these parameters approached those observed in non-diabetic controls, indicating substantial restoration of pancreatic islet structure and function. In conclusion, WSPP improves glycemic control and promotes beta-cell proliferation in diabetic rats, highlighting its potential as a natural, cost-effective therapeutic strategy for diabetes management.